Implementation Of Improvisation Techniques In Theater Extracurricular Training At Sman 1 Babat - Dani, Duwi Rahma; ., Arif Hidajad (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
Extracurricular activities are activities outside the main school curriculum (as a companion curriculum) that provide students with the opportunity to develop the potential, talents, interests, skills, personalities, and independence of students optimally. Similarly, SMAN 1 Babat gathers various extracurricular activities as supporting media to support the development of students' skills, interests, and talents. One of them is the Teater Air Extracurricular. In the training, this extracurricular applies exercise patterns with improvised techniques. The use of this technique is because trainers look for methods that are easy to be accepted by members as well as methods to encourage student creativity to foster self-confidence. The method in this study is a field research that uses a qualitative descriptive method approach with a phenomenological approach. Training in improvisation techniques in extracurricular activities consists of five types, namely: Solo Improvisation, Furniture Improvisation, Pair Improvisation, Story Series Improvisation, and Sound Improvisation, which are presented in the form of role play. The results of using improvisation techniques affect student creativity to foster self-confidence with stages of practice that support the development of creativity, artistic skills and student communication skills. Keywords: Technique, Improvisation, Extracurricular Theater Training